Impact of COVID-19 outbreak on esophageal cancer surgery in Northern Italy: lessons learned from a multicentric snapshot. Issue 6 (27th November 2020) - Rebecchi, Fabrizio; Arolfo, Simone; Ugliono, Elettra; Morino, Mario; Asti, Emanuele; Bonavina, Luigi; Borghi, Felice; Coratti, Andrea; Cossu, Andrea; De Manzoni, Giovanni; De Pascale, Stefano; Ferrari, Giovanni Carlo; et al.
Abstract: Coronavirus Disease-19 (COVID-19) outbreak has significantly burdened healthcare systems worldwide, leading to reorganization of healthcare services and reallocation of resources. The Italian Society for Study of Esophageal Diseases (SISME) conducted a national survey to evaluate changes in esophageal cancer management in a region severely struck by COVID-19 pandemic. A web-based questionnaire (26 items) was sent to 12 SISME units. Short-term outcomes of esophageal resections performed during the lockdown were compared with those achieved in the same period of 2019. Six (50%) centers had significant restrictions in their activity. However, overall number of resections did not decrease compared to 2019, while a higher rate of open esophageal resections was observed (40 vs. 21.7%; P  = 0.034). Surgery was delayed in 24 (36.9%) patients in 6 (50%) centers, mostly due to shortage of anesthesiologists, and occupation of intensive care unit beds from intubated COVID-19 patients. Indications for neoadjuvant chemo (radio) therapy were extended in 14% of patients. Separate COVID-19 hospital pathways were active in 11 (91.7%) units. COVID-19 screening protocols included nasopharyngeal swab in 91.7%, chest computed tomography scan in 8.3% and selective use of lung ultrasound in 75% of units. Postoperative interstitial pneumonia occurred in 1 (1.5%) patient. Recovery from COVID-19 pandemic was characterized by screening of patients in all units, and follow-up outpatient visits in only 33% of units. This survey shows that clinical strategies differed considerably among the 12 SISME centers. Evidence-based guidelines are needed to support the surgical esophageal community and to standardize clinical practice in case of further pandemics.